2014
DOI: 10.17129/botsci.112
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of an endangered cycad, Dioon sonorense (Zamiaceae): implications from variation of chloroplast DNA

Abstract: Abstract:The endemic species Dioon sonorense comprises the northernmost group of populations of Dioon, in Sonora, Mexico. Although it is endangered, only the southern populations are protected within a preservation area, while the remaining populations have not been taken into account in management plans or genealogical studies. Describing the intraspecifi c genealogy and the geographical structure of the genetic variation of D. sonorense may help in the identifi cation of units for further conservation. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The number of samples analysed also can influences the amount of genetic diversity detected. In cycads, a range of sample sizes have been used for phylogeographic studies, for example, one individual was used per population for Dioon sonorense (Zamiaceae), and moderate values of nucleotide diversity (h = 0.629) were obtained using the chloroplast region trnL-trnF (Gutiérrez-Ortega et al 2014). For Zamia paucijuga (Zamiaceae) with 8-10 individuals per population, high haplotid diversity was found using ITS2 (h = 0.843) and moderate diversity for the chloroplast region psbK-psbI (h = 0.669) (Nolasco-Soto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of samples analysed also can influences the amount of genetic diversity detected. In cycads, a range of sample sizes have been used for phylogeographic studies, for example, one individual was used per population for Dioon sonorense (Zamiaceae), and moderate values of nucleotide diversity (h = 0.629) were obtained using the chloroplast region trnL-trnF (Gutiérrez-Ortega et al 2014). For Zamia paucijuga (Zamiaceae) with 8-10 individuals per population, high haplotid diversity was found using ITS2 (h = 0.843) and moderate diversity for the chloroplast region psbK-psbI (h = 0.669) (Nolasco-Soto et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…for Z. paucijuga, with h = 0.669 and π = 0.0013 for the chloroplast region psbK-psbI and h = 0.843 and π = 0.0063 for ITS2. For Dioon sonorense,Gutiérrez-Ortega et al (2014) reported h = 0.629 and π = 0.0004 for the chloroplast region trnL-trnF. For the cycads in Mexico, there are reports of high genetic diversity in some species, with few populations and restricted habitats, as in the case of Zamia loddigesii Miq (González-Astorga et al 2006),.…”
mentioning
confidence: 99%
“…Either through the lens of 'classical' population genetics (Gonz alez-Astorga et al, 2003b, 2005, 2006 or through phylogeography (Huang et al, 2001;Chiang et al, 2009;Kyoda & Setoguchi, 2010;Zhan et al, 2011;Guti errez-Ortega, Kajita & Molinar-Freaner, 2014;Nolasco-Soto et al, 2015), the results of further work in this direction will allow the construction of ancestor-descendant hypotheses involving known populations, as well as the assessment of demographic history and genetic differentiation between these populations. In accordance with our population-genetic research programme, evolutionary inferences derived from these phylogeographical interventions will constitute the starting point in species recognition and circumscription.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the proposal of Chemnick et al (1997) to segregate D. sonorense from D. tomasellii was persuasive, the definition of D. sonorense only relies on the traits observed in the holotype of D. tomasellii var. sonorense of De Luca et al (1984), in spite that multiple authors (Sabato & De Luca 1985, Whitelock 2002, Gutiérrez-Ortega et al 2014, 2018c have reported important morphological variation among populations. During our field surveys in Sonora, Mexico, we confirmed such variation, especially when comparing the extremes of the distributional ranges of D. sonorense.…”
Section: Introductionmentioning
confidence: 94%
“…We have also evaluated the patterns of genetic variation among the Dioon populations in northwestern Mexico. The variation of chloroplast DNA (cpDNA) revealed two haplotypes (Gutiérrez-Ortega et al 2014, 2018a. One haplotype represents the populations from the Municipality of Álamos, Sonora, and the area of Río Fuerte in Northern Sinaloa; another haplotype is present in the populations from Municipality of Rosario to Sierra de Mazatán in central Sonora (Gutiérrez-Ortega et al 2014, 2018c.…”
Section: Species Delimitationmentioning
confidence: 99%